2004
DOI: 10.1080/08035250410015079
|View full text |Cite
|
Sign up to set email alerts
|

How do paediatricians communicate with children and parents?

Abstract: Communication is mainly instrumental. Doctors tend to direct the interview. Children's contribution is small. The participation of children needs to be encouraged as part of a patient-centred approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…Providers did not often elicit information from parents; nor did many parents volunteer information about their goals and preferences. Consistent with other observations of pediatric clinical encounters,(4, 16, 30, 31) very little effort was made to include patients, of any age, in decision making.…”
Section: Discussionmentioning
confidence: 72%
“…Providers did not often elicit information from parents; nor did many parents volunteer information about their goals and preferences. Consistent with other observations of pediatric clinical encounters,(4, 16, 30, 31) very little effort was made to include patients, of any age, in decision making.…”
Section: Discussionmentioning
confidence: 72%
“…Overall levels of child and adolescent verbal participation in clinical and research settings are low (Cox, Smith, Brown, & Fitzpatrick, 2009; Miller, Baker, Leek, Drotar, & Kodish, 2014; Sleath et al, 2011; van Staa & On Your Own Feet Research Group, 2011; Wassmer et al, 2004). Youth may not speak up in health care settings for a variety of reasons (Young, Dixon-Woods, Windridge, & Heney, 2003), and other factors, such as how the clinician or researcher speaks to them, may be more important in shaping their perceptions of the decision making process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, reducing variability in the target protocols may help to isolate the effects of decision making involvement on specific outcomes. Third, prior research in the clinical care context suggests that the dynamics of the child-parent-researcher triad may be important for future efforts to understand and facilitate assent to research participation (Savage & Callery, 2007; Tates, Meeuwesen, Elbers, & Bensing, 2002; van Staa & On Your Own Feet Research Group, 2011; Wassmer et al, 2004). Fourth, future research should utilize observational methods to measure children’s involvement (Miller et al, 2014; Olechnowicz, Eder, Simon, Zyzanski, & Kodish, 2002) and assess children immediately after the assent discussion, to reduce the potential effects of shared method variance and recall bias on the results.…”
Section: Research Agendamentioning
confidence: 99%
“…Prior research has found that children and adolescents with asthma are not actively involved during their medical visits [1-3]. Active involvement is important, especially for adolescents who have chronic diseases such as asthma, because interactive discussions with providers can help adolescents learn how to self-manage their treatment regimens [4].…”
Section: Introductionmentioning
confidence: 99%